COVID-19 bei jugendlichen Athleten: Diagnose und Return to Sports - Kriemler, S.; Siaplouras, J.; Förster, H.; Joisten, C. (sems-journal, 2021)
Summary: Children and adolescents should be active in sports as much and often as possible. If permitted by the federal government and the states/cantons, this can take place now or, depending on the state, in the near future. Strict adherence to hygiene and distance rules and staying away from sport in the case of SARS-CoV-2 typical symptoms can minimize the emergence of sources of infection and the transmission of the coronavirus. However, this is associated with a considerable psychological stress especially for children and adolscents. Although various diagnostic tests are available, the polymerase chain reaction (PCR) test is still considered the gold standard. However, a rapid antigen test can be a provisional procedure if time is of the essence and a PCR is postponed. The guidelines for an optimal "return to sports" should be based on the severity of the course after a corona infection and strictly adhered to because of the risk of myocarditis, which can potentially lead to sudden cardiac death. Zusammenfassung: Kinder und Jugendliche sollen sportlich aktiv sein, und zwar so viel und oft wie möglich. Dies kann, falls vom Bund und den Ländern/Kantonen erlaubt, bereits jetzt oder je nach Land in naher Zukunft stattfinden. Das strikte Befolgen von Hygiene- und Distanzregeln und das Fernbleiben vom Sport bei SARS-CoV-2-typischen Symptomen können das Entstehen von Infektionsherden und die Übertragung des Coronavirus minimieren, ist aber gerade bei Kindern und Jugendlichen mit einer grossen psychischen Belastung verbunden. Obwohl diverse diagnostische Tests zur Verfügung stehen, gilt der Polymerase-Kettenreaktion-Test (polymerase chain reaction, PCR-Test) nach wie vor als Goldstandard. Ein Antigen-Schnelltest kann jedoch ein provisorisches Vorgehen vorbahnen, wenn die Zeit drängt und eine PCR nachgeschoben wird. Die Richtlinien für einen optimalen Return to Sports sollen auf dem Schweregrad des Verlaufs nach einer Coronainfektion basieren und wegen des Risikos einer Myokarditis, welche potenziell zu einem plötzlichen Herztod führen kann, strikt eingehalten werden.